Rancang Bangun Sistem Informasi Penjualan Berbasis Web di Konter Titania Cell - Arianto, Bagas Ananda; Susena, Edy (STMIK Banjarbaru, 2025)
The sale of prepaid credit and data packages at Konter Titania Cell is still conducted manually, which carries risks such as recording errors, delayed reporting, and less accurate decision-making. This study aims to design and create a web-based sales information system to enhance the kiosk’s operational efficiency. The system development adopts the waterfall method, which includes the phases of analysis, design, implementation, testing, and maintenance. The system was built using the PHP programming language and MySQL database, and it is run on a local XAMPP server. Testing was carried out using the black-box testing method to ensure that each feature operates according to user needs. The test results show that the system can automatically record transactions, update inventory in real time, and generate accurate sales reports. This system has proven to improve operational efficiency and support effective decision-making.Keywords: Sales Information System; Phone Credit Sales; Waterfall Method; Micro-Small and Medium Enterprises; Web-Based Application AbstrakUsaha penjualan pulsa dan paket data di Konter Titania Cell masih dikerjakan secara manual, sehingga berisiko mengalami kesalahan pencatatan, keterlambatan laporan, dan pengambilan keputusan yang kurang tepat. Penelitian ini bertujuan untuk merancang dan menciptakan sistem informasi penjualan berbasis web untuk meningkatkan efisiensi operasional kios. Pengembangan sistem menerapkan metode waterfall yang meliputi fase analisis, desain, implementasi, pengujian, dan pemeliharaan. Sistem ini dibangun menggunakan bahasa pemrograman PHP dan database MySQL, serta dijalankan di server lokal XAMPP. Pengujian dilaksanakan dengan metode black-box testing untuk memastikan setiap fitur beroperasi sesuai dengan kebutuhan. Hasil ujian menunjukkan bahwa sistem dapat mencatat transaksi secara otomatis, memperbarui inventaris secara langsung, serta menyajikan laporan penjualan dengan tepat. Sistem ini terbukti dapat meningkatkan efisiensi operasional dan mendukung pengambilan keputusan.